Interferon gamma and interleukin 4 stimulate prolonged expression of inducible nitric oxide synthase in human airway epithelium through synthesis of soluble mediators. - Guo, F H (1997)
Human respiratory epithelium expresses inducible nitric oxide synthase (iNOS) continuously in vivo, however mechanisms responsible for maintenance of expression are not known. We show that IFNgamma is sufficient for induction of iNOS in primary human airway epithelial cells (HAEC) in vitro, and IL-4 potentiates IFNgamma-induced iNOS expression in HAEC through stabilization of iNOS mRNA. IFNgamma/IL-4- induced iNOS expression in HAEC was delayed in onset and prolonged with expression up to 1 wk. Removal of overlying culture media resulted in loss of expression, while transfer of conditioned media induced iNOS mRNA in other HAEC. IFNgamma and IL-4 stimulation activated STAT1 and STAT6 in HAEC, but conditioned media transfer to HAEC produced even higher levels of STAT1 activation than achieved by direct addition of cytokines. Although cytokine induction of iNOS was dependent on new protein synthesis, conditioned media induction of iNOS in HAEC was not. Further, removal of overlying culture media from cells at different times after cytokine stimulation demonstrated that mediator synthesis and/or secretion important for induction and maintenance of iNOS occurs early after cytokine stimulation. In conclusion, a combination of IFNgamma/ IL-4, which occurs naturally in the lung epithelial lining fluid, leads to maintenance of iNOS expression in human airway epithelium through production of soluble mediators and stabilization of mRNA.